The Prevalence and Factors Associated with Drug-induced Hepatitis in HIV-positive Tuberculosis Patients - Gurmeet Singh; Ceva Wicaksono Pitoyo (The Indonesian Society for Digestive Endoscopy, 2012)
Introduction: Tuberculosis (TB) have demonstrated a global increase since 1990 along with the increase of world’s population and the transmission of human immunodeficiency virus (HIV). Anti- tuberculosis drugs are very effective, but it may cause drug-induced hepatitis (DIH). The aim of this study was to assess the prevalence and association of several risk factos with the occurence of drug-induced hepatitis in HIV-positive tuberculosis patients. Method: We conducted a retrospective case-control study based on medical records of HIV-positive TB patients who seek medical attention to HIV Referral Center at Cipto Mangunkusumo Hospital between July 2008 and December 2010. Overall, we enrolled 168 medical records with 42 cases and 126 controls. Chi-square and logistic regression test analysis were conducted for analyzing risk factors of drug-induced hepatitis in HIV-positive tuberculosis patients. Results: Drug-induced hepatitis were found in 42 (8.04%) patients.The prevalence of DIH was highest among 35 (25.2%) male patients, aged 35 years old in 32 (26.0%) patients, with albumin level 3.5 g% in 10 (11.2%) patients, body mass index (BMI) 18.5 kg/m2 in 14 (18.4%) patients, CD4+ count 100 cells/mm3 in 29 (24.4%) patients, and those who received rifampicin (R), isoniazid (H), and pirazinamid (Z) regiments for their anti-tuberculosis drugs 24 (31.2%) patients. No risk factors were found to have statistically significant association with DIH. Conclusion: The prevalence of DIH is quite high. Although no risk factor was found statistically significant, but evaluation and liver biochemical examination should be carried out regularly in patients with DIH risk factors. Keywords: drug-induced hepatitis, tuberculosis, human immunodeficiency virus